Prevention of corruption: a tool to improve the quality of services in organisations - Jahani Doghezloo, Mansoureh; Mokhtari Dinani, Maryam; Rezaei Pandari, Abbas; Afshar Jahanshahi, Asghar (Inderscience, 2024)
Sport corruption is a global phenomenon, threatening the integrity of the sport industry. The goal of this study was to introduce and design a model of factors affecting the prevention of administrative-financial corruption in Iranian sport organisations. The population used in this research included all sport experts and executives in Iran. The number of 14 factors was accordingly selected as effective in preventing administrative-financial corruption. The relationship between these factors was analysed using interpretive structural modelling (ISM). Based on results, the factors fell into four categories: the factors 'fairness in payment' and 'avoidance of granting special privileges' at the highest (first) level while 'promotion of accountability' was at the lowest (fourth) level. 'Accountability enhancement' was also found as an independent variable in the model. Results widely support the view that 'promoting accountability' is the most important factor in the prevention of corruption in Iranian sports organisations. ©International Journal of Productivity and Quality Management (IJPQM), Vol. 42, No. 1, 2024.